Case of acquired haemophilia a in Southeast Asia following COVID-19 vaccine. Issue 3 (9th March 2022) - Ai Vuen, Lee; Aun Su-Yin, Evelyn; Naila Kori, Ahlam; Shah, TM
Abstract : Acquired haemophilia A (AHA) is a rare bleeding disorder with high morbidity and mortality, but it is eminently treatable if diagnosis and treatment are prompt. We report a case of AHA in Southeast Asia following the administration of the Pfizer-BioNTech COVID-19 vaccine. A man in his 80s developed multiple bruises 2 weeks after his first dose of the COVID-19 vaccine. Diagnosis was delayed due to his cognitive impairment and low clinical suspicion. This led to a representation with worsening ecchymosis, a left thigh haematoma and symptomatic anaemia. Laboratory testing was notable for an isolated prolongation of the activated partial thromboplastin time, which remained uncorrected in the mixing test. Further testing confirmed the presence of factor VIII (FVIII) inhibitors and low FVIII titres of 6.7%. He responded to treatment with intravenous methylprednisolone and recombinant activated FVII. Screening for autoimmune diseases and malignancies was negative.